Role of pleural fluid analysis in establishing the diagnosis of pleural effusion Experience in College of Medical Sciences-Teaching Hospital, Bharatpur, Nepal - Swamy, GG; Rao, TMV Prasada; Sunitha, P; Madhuravani, S (Journal of College of Medical Sciences-Nepal, 2012)
Aspiration of serous cavities is a simple and relatively non-invasive technique to achieve a diagnosis. The information provided by body fluid analysis serves several functions; it is a complete diagnostic modality which aims at pointing out the etiology of effusion as well as in certain cases, a means of prognostication of the disease process. The diagnostic performance of the cytological study of the fluid may be attributable to the fact that the cell population present in sediment. Thus, this study was aimed to assess the role of pleural fluid analysis in establishing the cause of pleural effusion. A retrospective study was carried out in the Department of Pathology, College of Medical Sciences Teaching Hospital, Bharatpur from July 2008 to July 2010. Two hundred samples of pleural fluid were examined for total cell count, cell type and cellular features along with biochemical study to find out the level of protein, glucose and chloride. In two hundred samples, 80% were exudative and 20% were transudative. Cirrhosis and congestive cardiac failure were commonest causative factors in transudatives. The cases of Tuberculosis were predominant in exudatives followed by malignancies. In the samples from all the tuberculosis patients, lymphocytes were the predominant cell type. Most of malignant effusions were exudatives. The primary site could be assessed by cytological examination in more than fifty percent of cases. The present study demonstrates that the most useful test in establishing the diagnosis of pleural effusion is pleural fluid analysis which includes mainly its cytology and cell count. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 36-45 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6724